Prevalence of vancomycin resistance and multiple drug resistance in enterococci in equids in North India - Bhoj Raj Singh (Journal of Infection in Developing Countries)
Introduction: Vancomycin resistant and multi-drug-resistant enterococci are the major emerging pathogens in surgical, neonatal, and tertiary care units. Methodology: In this study, 267 enterococci from different clinical and non-clinical samples of equine origin were tested for their antimicrobial drug sensitivity against 19 antimicrobials using disc diffusion method. Results: A total of 80.2% enterococci tested were resistant to vancomycin and 99.6% to multiple-drugs. There was a significant association between haemolytic potential and vancomycin resistance (χ2, 0.00). Enterococci isolates from healthy equids were significantly (χ2, 0.04) less resistant to vancomycin than the isolates from clinically sick animals. Besides vancomycin sensitivity, isolates were also tested for 18 more antimicrobial drugs; maximum numbers of isolates were sensitive to imipenem (75%) followed by tetracycline (60%), amoxicillin+clavulanic acid (54%), and minimum for cefdinir (4%). Conclusion: More than 80% strains of enterococci of equine origin were found resistant to vancomycin and 99.6% were multiple-drug resistant in Northern India. High prevalence of VRE and MDRE in healthy equids might be a potential danger for the health of persons in equine contact.